2017
DOI: 10.1186/s12906-016-1541-y
|View full text |Cite
|
Sign up to set email alerts
|

Litchi seed extract inhibits epidermal growth factor receptor signaling and growth of Two Non-small cell lung carcinoma cells

Abstract: BackgroundLitchi seeds possess rich amounts of phenolics and have been shown to inhibit proliferation of several types of cancer cells. However, the suppression of EGFR signaling in non-small cell lung cancer (NSCLC) by litchi seed extract (LCSE) has not been fully understood.MethodsIn this study, the effects of LCSE on EGFR signaling, cell proliferation, the cell cycle and apoptosis in A549 adenocarcinoma cells and NCI- H661 large-cell carcinoma cells were examined.ResultsThe results demonstrated that LCSE po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 30 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Like what was observed in prostate cancer cells, hydroalcoholic extract of the seed potentiated anticancer properties in lung cancer cells (A549 and NCI‐ H661 cells) by inhibiting cell growth, upregulating proapoptotic proteins, and downregulating epidermal growth factor receptor‐mediated activation of Akt and Erk‐1/‐2 signaling (Chung et al., 2017). Furthermore, the anticancer property of litchi fruit peel has been shown in human hepatocellular carcinoma cell.…”
Section: Pharmacological Phytochemical and Toxicological Aspects Of Litchi Fruit Seed And Peelmentioning
confidence: 80%
See 1 more Smart Citation
“…Like what was observed in prostate cancer cells, hydroalcoholic extract of the seed potentiated anticancer properties in lung cancer cells (A549 and NCI‐ H661 cells) by inhibiting cell growth, upregulating proapoptotic proteins, and downregulating epidermal growth factor receptor‐mediated activation of Akt and Erk‐1/‐2 signaling (Chung et al., 2017). Furthermore, the anticancer property of litchi fruit peel has been shown in human hepatocellular carcinoma cell.…”
Section: Pharmacological Phytochemical and Toxicological Aspects Of Litchi Fruit Seed And Peelmentioning
confidence: 80%
“…Similarly, up to 3,750 µg/ml of the seed's resin‐purified 70% ethanol extract was not cytotoxic in normal BV‐2 cells (Zhao et al., 2018), while up to 10 µg/ml of the peel's ethyl acetate fraction (from the 70% extract) was not cytotoxic the normal P19 neuronal cells (Tadtong et al., 2013). Also, no severe toxicity was caused by litchi seed's 70% ethanol extract in normal lung cells (MRC‐5 cells) (Chung et al., 2017). Interestingly, the above‐mentioned non‐toxic concentrations of litchi peel and seed extracts/fractions/isolates were above the effective bioactive doses, suggesting that litchi fruit seed and peel may not pose safety concerns.…”
Section: Pharmacological Phytochemical and Toxicological Aspects Of Litchi Fruit Seed And Peelmentioning
confidence: 99%
“…14 Other research has shown that litchi seed extract could suppress epidermal growth factor receptor signalling and inhibited non-small cell lung cancer cell growth. 15 In this experiment, serum pharmacological methods were used to observe the effect of semen litchi drug serum on the proliferation inhibition rate of human hepatoma HepG2 cells. The results of this study indicate that semen litchi drug serum has a good effect on inhibiting proliferation of HepG2 cells, and showing a dose-time dependent effect.…”
Section: Discussionmentioning
confidence: 99%
“…Both cell culture media were supplemented with FBS (10%, v/v), sodium pyruvate (1 mM), penicillin (100 units/ml) and streptomycin (100 μg/ml). MRC-5 cells, which were used as control non-cancerous lung cells as before 29 31 , were cultured in MEM containing FBS, sodium pyruvate, penicillin and streptomycin as above. All cells were incubated at 37 °C in standard cell culture conditions.…”
Section: Methodsmentioning
confidence: 99%